From Text to Transformation: Reviewing Sheikh Nawawi's Educational Philosophy - Haki, Ubay; Hazarika, Anurag (Assyfa Journal of Islamic Studies, 2024)
This research is motivated by the importance of understanding the contribution of Syekh Nawawi's thoughts in developing Islamic education in Indonesia. Syekh Nawawi, a great cleric from Banten, has significantly contributed to science, Aqidah and History. This research aims to identify and analyze research trends related to Syekh Nawawi's educational philosophy and dig deeper into the relevance of his thinking in the context of learning science and Aqidah and Banten history. The problem raised is the lack of in-depth understanding of the application of Sheikh Nawawi's thoughts in modern education. This research uses bibliometric methods with VOSviewer software to identify research trends from 2004 to 2024 and a systematic literature review (SLR) using the PRISMA technique with data from the Scopus database. Keywords used include "Sheikh Nawawi," "educational philosophy," "science learning," "Aqidah," and "Banten history." Significant findings show that Sheikh Nawawi's thoughts remain relevant and can be integrated into the current educational curriculum. Trend analysis reveals increasing interest in the study of Sheikh Nawawi's thoughts. This study differs from previous studies because it uses a more comprehensive methodological approach and in-depth bibliometric analysis. It is hoped that the research results can become an essential reference in developing learning modules that focus not only on cognitive aspects but also on spiritual and historical aspects, especially in the educational context in Banten.